Autonomy-Supportive Parenting and Autonomy-Supportive Sibling Interactions: The Role of Mothers’ and Siblings’ Psychological Need Satisfaction - Kaap-Deeder, Jolene van der (2015)
Autonomy-supportive parenting yields manifold benefits. To gain more insight into the family-level dynamics involved in autonomy-supportive parenting, the present study addressed three issues. First, on the basis of self-determination theory, we examined whether mothers’ satisfaction of the psychological needs for autonomy, competence, and relatedness related to autonomy-supportive parenting. Second, we investigated maternal autonomy support as an intervening variable in the mother–child similarity in psychological need satisfaction. Third, we examined associations between autonomy-supportive parenting and autonomy-supportive sibling interactions. Participants were 154 mothers (M age = 39.45, SD = 3.96) and their two elementary school-age children (M age = 8.54, SD = 0.89 and M age = 10.38, SD = 0.87). Although mothers’ psychological need satisfaction related only to maternal autonomy support in the younger siblings, autonomy-supportive parenting related to psychological need satisfaction in both siblings and to an autonomy-supportive interaction style between siblings. We discuss the importance of maternal autonomy support for family-level dynamics.